Using Secondary School Students’ Perceptions to Develop a Structural Model for Attitude to Christianity - Dorman, Jeffrey P. (International journal of education and religion, 2000)
Over the past 30 years, independent lines of research in the fields of classroom environment and student attitudes to Christianity have been conducted. This research brought these two fields together by hypothesizing a model for the relationship among age, gender, students’ perceptions of religion classroom environment, students’ religious behavior and attitudes to Christianity. Responses from 815 Australian Catholic secondary school students on four attitude to Christianity scales, four classroom environment scales and the religious behavior of students and their parents were analyzed. Confirmatory factor analysis was used to validate the structure of the classroom environment and attitude to Christianity measures. Goodness of fit indices obtained from structural equation modeling revealed that the hypothesized model was a satisfactory fit to the data. Statistically significant path coefficients for the influence of students’ religious behavior and students’ perceptions of the religion classroom environment on students’ attitude to Christianity were found.